Molecular cloning of the recA gene and construction of a recA strain of Francisella novicida. - Berg, J M (1992)
A gene locus that is functionally analogous to the recA gene of Escherichia coli was molecularly cloned from Francisella novicida. The cloned gene was found to suppress the sensitivity of an E. coli strain to DNA-damaging agents and to support genetic recombination in E. coli. After transposon mutagenesis, the recA-like gene locus was returned to F. novicida and a UV-sensitive F. novicida strain was isolated. In contrast to the wild-type strain, this UV-sensitive strain could not be transformed with chromosomal DNA.